Nature as a subject of rights and its constitutional interpretation: Interculturality and worldview of original peoples - Barahona Néjer, Alexander (2020)
This article contributes to the construction of a constitutional method that I considers about sumak kawsay rule and its elements in the interpretation of nature as a subject of rights, both in jurisprudence and legal ethics. In this way, interculturality is considered as the foundation of an epistemology that amalgamates the various worldviews that conjugates the Constitution. Therefore, at first, will be approached the sumak kawsay-nature relationship, exposing the notions that, from the indigenous worldview, base its recognition as a rights subject. Subsequently, will be analyzed the special relationship that free people or voluntary isolation peoples have with nature, approaching their worldview in order to incorporate their focus on constitutional hermeneutics. Finally, as a corollary, the pragmatic dimension of intercultural interpretation and its relevance in the Ecuadorian constitutional paradigm is emphasized.